Answer:
D. 5x 2+12x−7
Step-by-step explanation:
(0-(2•(x2)+8x)-9)+4x)+7x2)+2
(0-2x2)+8x)-9)+4x)+7x2)+2
Factoring 5x2+12x-7
The first term is, 5x2 its coefficient is 5 .
The middle term is, +12x its coefficient is 12 .
The last term, "the constant", is -7
Step-1 : Multiply the coefficient of the first term by the constant 5 • -7 = -35
Step-2 : Find two factors of -35 whose sum equals the coefficient of the middle term, which is 12 .
-35 + 1 = -34
-7+ 5 = -2
-5+ 7 = 2
-1+ 35= 34
No two such factors can be found
Trinomial can not be factored